From the Other Side Women, Gender, & Immigrant Life in the U.S., 1820-1990 - Gabaccia, Donna (Indiana University Press, 1994)
While most histories of immigrants in the United States begin with the experiences of migratory men disguised as genderless humans, From the Other Side instead begins with the experiences of migratory women. But though centered on women, its analysis does not stop with them. Immigrant women cannot be studied apart from men of their own backgrounds, nor apart from American women. As mobile and culturally distinctive outsiders, foreign-born women shared key experiences with foreign-born men, as well as with native-born women who migrated from country to city, poor women who struggled to survive and prosper, and native-born minorities seeking dignity and acceptance as Americans. Immigrants' daughters, in turn, encountered elite majority women eager to guide them toward American-style womanly behavior.